2007
DOI: 10.1111/j.1745-7254.2007.00607.x
|View full text |Cite
|
Sign up to set email alerts
|

Alendronate inhibits cell invasion and MMP-2 secretion in human chondrosarcoma cell line

Abstract: Aim: Chondrosarcoma is a malignant primary bone tumor that responds poorly to both chemotherapy and radiation therapy. The aim of the present study was to investigate the effect of alendronate, a bisphosphonate, on the invasion and migration of human chondrosarcoma cells (JJ012). Methods: JJ012 cells were treated with alendronate of various concentrations up to 100 µmol/L for a specified period, and then gelatin zymography and matrigel invasion assay was performed to study the effects of alendronate on matrix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…As showed previously by other studies [4,6,11], we observed MMP-2 activation and no effect of pamidronate in this result. Several studies showed inhibit MMP-2 activation when bisphosphonates were used [20][21][22]; however, Gonçalves et al [43] indicated that pamidronate did not affect MMP activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As showed previously by other studies [4,6,11], we observed MMP-2 activation and no effect of pamidronate in this result. Several studies showed inhibit MMP-2 activation when bisphosphonates were used [20][21][22]; however, Gonçalves et al [43] indicated that pamidronate did not affect MMP activation.…”
Section: Discussionmentioning
confidence: 99%
“…The recent use of bisphosphonates was associated with decreased MMP activation [20][21][22]. In addition, bisphosphonates treatment in patients with several types of cancer decreased serum lipid hydroperoxide levels and increased serum glutathione peroxidase levels [23].…”
Section: Introductionmentioning
confidence: 99%
“…Because N-BPs have been shown to exert anti-tumour effects in vitro, recent works have been performed on chondrosarcoma cell lines. Thus, Lai et al demonstrated that alendronate inhibits JJ012 chondrosarcoma cell invasion and MMP-2 expression/activity in a dosedependent manner [88]. These data have been confirmed by Susa et al in 2009 who showed that alendronate decreased the viability of human CS-1 chondrosarcoma cell line by inhibiting simultaneously proliferation and migration [89].…”
Section: Bisphosphonates and Treatment Of Chondro-sarcomasmentioning
confidence: 73%
“…4D). Aln has been shown to reduce the activity and mRNA levels of MMP-2 and inhibit cell invasion in the chondrosarcoma cell line (39). APC can inhibit MMP-9 via NF-κB, while at the same time promoting MMP-2 activity (34).…”
Section: Apc Protects Endothelial Cells From Bisphosphonate-induced Dmentioning
confidence: 99%